Design and fabrication of a holey fiber microfluidic device with transverse micro-channel - Hu, Dora Juan Juan; Cui, Ying; Lim, Jun Long; Shum, Perry Ping; Humbert, Georges; Auguste, Jean-Louis; Wang, Yixin (Photonics Letters of Poland, 2014)
In this report, we present a design of holey fiber structure with six air holes in the cladding and a transverse microfluidic channel intersecting the silica core for liquid detection purpose. The simulation results suggest an improved refractive index sensitivity of the proposed structure compared to that of a single mode fiber with similar transverse channel. The proposed holey fiber structures are fabricated and characterized. Full Text: PDF References J.C. Knight, J. Arriaga, T.A. Birks, A. Ortigosa-Blanch, W.J. Wadsworth and P.St.J. Russell, "Anomalous dispersion in photonic crystal fiber", IEEE Photon. Technol. Lett. 12, 807 (2000) CrossRef D.J.J. Hu, P. Shum, G. Ren and C. Lu, "Hole-assisted lightguide fibers with small negative dispersion and low dispersion slope", App. Opt. 47, 5061 (2008) CrossRef P.St.J. Russell, P. Hölzer, W. Chang, A. Abdolvand and J. C. Travers, "Hollow-core photonic crystal fibres for gas-based nonlinear optics", Nature Photonics, 8, 278 (2014) CrossRef D. J. J. Hu, P. Shum, C. Lu and G. Ren, "Dispersion-flattened polarization-maintaining photonic crystal fiber for nonlinear applications", Opt. Comm. 282, 4072 (2009) CrossRef K. Milenko, D. J. J. Hu, P. P. Shum, T. Zhang, J. L. Lim, Y. Wang, T. R. Wolinski, H. Wei and W. Tong, "Photonic crystal fiber tip interferometer for refractive index sensing", Opt. Lett., 37, 1373 (2012) CrossRef D. J. J. Hu, Y. Wang, J. L. Lim, T. Zhang, K. Mileńko, Z. Chen, M. Jiang, G. Wang, F. Luan, P. P. Shum, Q. Sun, H. Wei, W. Tong and T. R. Woliński, "Novel Miniaturized Fabry–Perot Refractometer Based on a Simplified Hollow-Core Fiber With a Hollow Silica Sphere Tip", IEEE Sensors Journal, 12, 1239 (2012) CrossRef M.T. Myaing, J.Y. Ye and T.B. Norris, "Enhanced two-photon biosensing with double-clad photonic crystal fibers", Opt. Lett., 28, 1224 (2003) CrossRef D. J. J. Hu, J. L. Lim, M. K. Park, L. T.-H. Kao and Y. Wang, "Photonic Crystal Fiber-Based Interferometric Biosensor for Streptavidin and Biotin Detection", IEEE J. Sel. Top. Quant. Electron., 18, 1293 (2012) CrossRef D. J. J. Hu, J. L. Lim, Y. Cui, K. Milenko, Y. Wang, P. P. Shum and T. Wolinski, "Fabrication and Characterization of a Highly Temperature Sensitive Device Based on Nematic Liquid Crystal-Filled Photonic Crystal Fiber", IEEE Photonics Journal, 4, 1248 (2012). CrossRef Y. Cui, P.P. Shum, D. J. J. Hu, G. Wang, G. Humbert and X.-Q Dinh, "Temperature Sensor by Using Selectively Filled Photonic Crystal Fiber Sagnac Interferometer", IEEE Photonics Journal, 4, 1801 (2012) CrossRef D. J. J. Hu, P.P. Shum, J.L. Lim, Y. Cui, K. Milenko, Y. Wang and T. Wolinski, "A Compact and Temperature-Sensitive Directional Coupler Based on Photonic Crystal Fiber Filled With Liquid Crystal 6CHBT", IEEE Photonics Journal, 4, 2010 (2012) CrossRef Dinish U. S, Chit Yaw Fu, Kiat Seng Soh, Ramaswamy Bhuvaneswari, Anil Kumar and Malini Olivo, "Highly sensitive SERS detection of cancer proteins in low sample volume using hollow core photonic crystal fiber", Biosensors and Bioelectronics, 33, 293 (2012) CrossRef K. Zhou, Z. Yan, L. Zhang, and I. Bennion, "Refractometer based on fiber Bragg grating Fabry-Pérot cavity embedded with a narrow microchannel," Opt. Express 19, 11769-11779 (2011). CrossRef J. Petrovic, Y. Lai, and I. Bennion, "Numerical and experimental study of microfluidic devices in step-index optical fibers", Appl. Opt. 47, 1410-1416 (2008). CrossRef